The role of the seed sector in Italy for a modern and competitive agriculture - Nardi, Marco (Italian Journal of Agronomy, 2016)
The high number of seed companies that are active on the Italian market provides our agriculture with the most appropriate varieties. Italy is particularly suited for growing seed crops: thanks to its favourable environmental conditions and also to the high level of professional skills of companies and farmers, Italy plays a leading role in the multiplication and export of vegetables, rice and sugarbeet seeds. In many cases, seeds grown in Italy are exported for conditioning and then re-imported for distribution to the end users. In 2014 the annual turnover for seed sales in Italy was approximately EUR 680-700 million, at wholesale level and excluding the incidence of chemical seed treatment. The difference between the value of seed imports and exports has been negative in the last few years of an average amount of approximately EUR 100 million. At the moment there are about 300 seed companies trading on the Italian market (220 for agricultural plant species and 80 for vegetable species). Seed multiplication is also a great income opportunity for farmers: every year approximately 15,000 Italian farmers devote around 220,000 ha to grow seed crops. The use of high quality seed today represents not only a simple means to start a new cultivation, with a healthy, well identified and traced product, but an efficient way to transfer plant breeding results to farmers, in order to cope with the need of innovation and sustainability. Through the purchase and planting of certified seeds farmers support and strengthen variety research and innovation.